Flexible peer selection mechanisms for future Internet applications - Sousa, Pedro (2009)
This paper focuses on the development of solutions able to enhance the peer selection semantics supported by P2P based applications. The proposed framework relies on the concept of a flexible P2P tracker able to support multiple versatile peer selection procedures that might be activated and configured during the application lifetime. The devised flexible tracker may also resort to additional cross-layer informations provided by the network level or other external entities. Using a BitTorrentlike P2P approach as a case study, the proposed solution fosters the capabilities of P2P applications to differentiate, benefit or penalize specific peers, also giving ground for the development of advanced applications based on the P2P paradigm.